2017
DOI: 10.3168/jds.2016-11668
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Mammary gland ultrasonography to evaluate mammary parenchymal composition in prepubertal heifers

Abstract: Bovine mammary gland development studies are often terminal or involve invasive biopsy procedures. Therefore, noninvasive means of assessing mammary development should be considered as alternative methods in live animals. The objective was to test if mammary ultrasonography can be used as a noninvasive way to estimate mammary parenchyma (PAR) composition in prepubertal dairy heifers with different average daily body weight gains. In the 84 d preceding, the ultrasound exam heifers were maintained in 1 of 3 trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 14 publications
0
25
0
3
Order By: Relevance
“…Therefore, there will be less precision using the technique than when the PAR and MFP are dissected from glands and weighed after harvesting. Despite this limitation, other investigators have indicated that gross demarcations between PAR and MFP can be identified using the intensity of pixel brightness [PAR is hypoechoic (black) and MFP is hyperechoic (white)] to aid tracing the outlines of PAR using software (Esselburn et al, 2015;Albino et al, 2017;Furini et al, 2018). For the current study, we reasoned that using software to measure the volume of mammary glands from traced outlines was not necessary because (1) the tracing method also relies on the ability of an observer to interpret where the demarcations are, (2) a single image will usually not capture the entire gland of larger glands and, therefore, superimposed images are required, and finally, (3) the tracing method is very time consuming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there will be less precision using the technique than when the PAR and MFP are dissected from glands and weighed after harvesting. Despite this limitation, other investigators have indicated that gross demarcations between PAR and MFP can be identified using the intensity of pixel brightness [PAR is hypoechoic (black) and MFP is hyperechoic (white)] to aid tracing the outlines of PAR using software (Esselburn et al, 2015;Albino et al, 2017;Furini et al, 2018). For the current study, we reasoned that using software to measure the volume of mammary glands from traced outlines was not necessary because (1) the tracing method also relies on the ability of an observer to interpret where the demarcations are, (2) a single image will usually not capture the entire gland of larger glands and, therefore, superimposed images are required, and finally, (3) the tracing method is very time consuming.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound has increasingly been used in studies on mammary anatomy and milk storage (Bruckmaier and Blum, 1992;Ayadi et al, 2003;Franz et al, 2009), and to monitor the development of mammary glands of replacement heifers to understand what influence diet has on these tissues and to evaluate what influence changes in growth of these tissues have on subsequent lactation (Nishimura et al, 2011;Albino et al, 2015;Esselburn et al, 2015;Albino et al, 2017;Furini et al, 2018). Notably, the technique is noninvasive and has the potential to be objective.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound allows a real-time visualization of various tissues [11] and has been used to evaluate various internal structures of the udder such as the UC [16] and the teat [10,[18][19][20]. Several studies have performed ultrasounds of the UC to demonstrate normal mammary gland features in dairy heifers [11,28] and in lactating cows [16,21,29,30], and other authors have evaluated the non-physiological pattern in a sick mammary gland [31]. To the best of our knowledge, no studies have evaluated the size of the UC in dry cows.…”
Section: Discussionmentioning
confidence: 99%
“…Mammary gland ultrasound images were taken using a micro-convex transducer (Mindray DP2200, Shenzhen, China), operating at a frequency of 6 MHz. Images were taken of each mammary quarter [43].…”
Section: Mammary Gland Ultrasoundmentioning
confidence: 99%